The Wikipedia Republic of Literary Characters - Paula Wojcik; Bastian Bunzeck; Sina Zarrieß (Journal of Cultural Analytics)
Literary characters do not receive the same attention from literary scholars as other components of literature (i.e. the narrative, theme, motif). In contrast to this lack of interest, various studies have shown that characters in particular play an important role for readers. We draw on this observation to explore a user-oriented notion of World Literature according to the collaborative encyclopedia Wikipedia. Based on its language-independent taxonomy Wikidata, we collect data from 321 Wikipedia editions on more than 7000 characters presented on more than 19000 independent character pages across the various language editions. We use this data to build a network that represents affiliations of characters to Wikipedia languages, which leads us to question some of the established presumptions towards key-concepts in World Literature studies such as the notion of major and minor, the center-periphery opposition or the canon.